Delo medicinskih sester pri spremljanju otrok z lymsko boreliozo - Jagodic, Veronika (Obzornik zdravstvene nege, 2004)
In the article nurse activities with parents to prevent Lyme borreliosis in their children at the Department of Infectious Diseases in Ljubljana are presented. The aim of the study was to determine differences in knowledge and behaviour in parents for preventing the disease in children with and without Lyme borreliosis. The study was performed from July l, 2001 through September 31, 2001 at the Department of Infectious Diseases in Ljubljana. 70 parents of children, searching medical help because of Lyme borreliosis were compared with 70 parents of children, visiting our department because of other reasons.Data were collected with a case report form and analyzed with descriptive statistic methods. The study goal was to evaluate and improve the effectiveness of nurse activities at the Department of Infectious Diseases in Ljubljana in teaching parents to prevent Lyme borreliosis in their children. The results showed that the knowledge Lyme borreliosis in parents of children with Lyme borreliosis is higher than in parents without direct contact with this disease. Medical counselling of parents is performed in informal way. Theauthor elaborated instructions for parents how to prevent Lyme borreliosis in their children with non-specific measures.
Keywords: ankete; Child; Health Education; Lyme borelioza; Lyme Disease; Lymska bolezen; medicinske sestre; Nursing; otroci; Otrok; Parents; Prevention And Control; Questionnaires; Starši; zdravstvena nega; Zdravstvena vzgoja